Influence of Culture and Socio-Financial Elements on the Career Choice of Students in Bwari Area Council in Abuja, Nigeria - Oparaduru, John Onyemauche; Ciroma, Kwahi Wada (NIU Journal of Humanities, 2023)
One of the most important decisions a person makes is their career choice, which will shape their future. The investigation examined cultural factors' impact on Bwari Area Council students' career choices in Abuja, Nigeria. Two hypotheses guided the research. All Bwari Area Council senior secondary school students are studied. The study includes all SSII male and female seniors. The study selected 315 SSII students using simple random sampling. The study included 63 students from each of the five schools. The self-structured questionnaire Influence of Sociocultural Factors on the Career Choice of Students (ISCFCCCS) with sub-instruments (Cultural and Socioeconomic Influences on Career Choice) and Career Choice Questionnaire (CCQ) with reliability coefficients of 0.88, 0.86, and 0.75 were used to collect data. Data was analysed using descriptive and inferential statistics. The study found that culture and parents' socioeconomic status strongly influence students' career choices. The study recommends that school leaders teach students about social factors that may influence their career choice. Parents should also stop pushing their kids into careers they don't fit into. Guardians should be cautious about pushing their children toward unrealistic careers. Parents should also work with school advising or professional guides to help their children choose smart careers. Keywords: Sociocultural, Financial status, Career choice Culture, Understudies, Influence